Compassionate care during withdrawal of treatment: A secondary analysis of ICU nurses' experiences. (December 2018) - Efstathiou, Nikolaos; Ives, Jonathan
Background: Withdrawal of treatment is a common practice in intensive care units when treatment is considered futile. Compassion is an important aspect of care; however, it has not been explored much within the context of treatment withdrawal in intensive care units. Objectives: The aim was to examine how concepts of compassion are framed, utilised and communicated by intensive care nurses in the context of treatment withdrawal. Design: The study employed a qualitative approach conducting secondary analysis of an original data set. In the primary study, 13 nurses were recruited from three intensive care units within a large hospital in United Kingdom. Deductive framework analysis was used to analyse the data in relation to compassionate care. Ethical considerations: The primary study was approved by the local Research Ethics Committee and the hospital's Research and Development services. Findings: Compassionate care was mostly directed to the patient's family and was demonstrated through care and emotional support to the family. It was predominantly expressed through attempts to maintain the patient's dignity by controlling symptoms, maintaining patient cleanliness and removing technical apparatus. Conclusion: This study's findings provide insight about compassionate care during treatment withdrawal which could help to understand and develop further clinicians' roles. Prioritising the family over the patient raised concerns among nurses, who motivated by compassion, may feel justified in taking measures that are in the interests of the family rather than the patient. Further work is needed to explore the ethics of this.